An in vivo Cell-Based Delivery Platform for Zinc Finger Artificial Transcription Factors in Pre-clinical Animal Models - Deng, Peter; Halmai, Julian A. N. M.; Beitnere, Ulrika; Cameron, David; Martinez, Michele L.; Lee, Charles C.; Waldo, Jennifer J.; Thongphanh, Krista; Adhikari, Anna; Copping, Nycole; Petkova, Stela P.; Lee, Ruth D.; et al. (Frontiers in Molecular Neuroscience, 2022)
Zinc finger, transcription activator-like effectors, and CRISPR/Cas9 therapies to regulate gene expression are becoming viable strategies to treat genetic disorders, although effective in vivo delivery systems for these proteins remains a major translational hurdle. We describe the use of a mesenchymal stem/stromal cell (MSC)-based delivery system for the secretion of a zinc finger protein (ZF-MSC) in transgenic mouse models and young rhesus monkeys. Secreted ZF protein from mouse ZF-MSC was detectable within the hippocampus one week following intracranial or cisterna magna injection. Secreted ZF activated the imprinted paternal Ube3a in a transgenic reporter mouse and ameliorated motor deficits in a Ube3a deletion Angelman Syndrome mouse. Intrathecally administered autologous rhesus MSCs were well-tolerated for three weeks following administration and secreted ZF protein was detectable within the cerebrospinal fluid, midbrain, and spinal cord. This approach has the potential to provide a less-invasive means to deliver gene therapies into the central nervous system.